How Do We Talk With People Living With Dementia About Future Care: A Scoping Review - Visser, Mandy; Smaling, Hanneke J. A.; Parker, Deborah; van der Steen, Jenny T. (Frontiers in Psychology, 2022)
A diagnosis of dementia often comes with difficulties in understanding a conversational context and expressing how one feels. So far, research on how to facilitate advance care planning (ACP) for people with dementia focused on defining relevant themes and topics for conversations, or on how to formalize decisions made by surrogate decision makers, e.g., family members. The aim of this review is to provide a better scope of the existing research on practical communication aspects related to dementia in ACP conversations. In November 2020, seven databases were searched to select papers for inclusion (Proquest, Medline, Embase, Scopus, Psycinfo, Amed and Cinahl). This search was updated in December 2021. The search strategy consisted of three tiers (related terms to “dementia”, “communication” and “ACP”), intersected by using the Boolean term “AND”, and resulted in 787 studies. Two researchers followed explicit criteria for two sequential levels of screening, based on titles and abstracts and full papers. A total of 22 studies were included for data analysis. Seven topics (i.e., importance of having ACP conversations, knowledge gap, inclusion of people with dementia in ACP conversations, policy versus practice, adapting to cognitive changes, adapting to psychosocial changes, and adapting to emotional changes) emerged clustered around two themes (i.e., communicating with people with dementia in ACP, and changes in communication due to dementia). This scoping review provides practical suggestions for healthcare professionals to improve ACP communication and uncovered gaps in research on communication aspects related to dementia in ACP conversations, such as nonverbal behavior, timing and implementation, and personal preferences.